2016
DOI: 10.1007/s11888-016-0324-7
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Best Radiosensitizing Agent in the Treatment of Locally Advanced Rectal Cancer?

Abstract: Over the past several decades, the management of localized rectal cancer has evolved from surgery alone as the definitive treatment to incorporating both radiation and chemotherapy to improve rates of local control and disease-free survival. Several chemoradiation regimens have been tested with different mechanisms of action, efficacy, and toxicity. There is little debate that concurrent radiation and a fluoropyrimidine (5-fluorouracil (5-FU) or capecitabine) is the current standard of care prior to total meso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Irinotecan, a topoisomerase (TOPO) 1 inhibitor, inhibits religation of single‐strand DNA breaks through the formation of camptothecin 11–TOPO‐1–DNA complexes. A preclinical study has demonstrated irinotecan to be not only a feasible addition to 5‐FU chemotherapy, but also a potent radiosensitizing agent in colorectal cancer, even under hypoxic conditions.…”
Section: Additional Chemotherapy Agents To Enhance Radiosensitivitymentioning
confidence: 99%
“…Irinotecan, a topoisomerase (TOPO) 1 inhibitor, inhibits religation of single‐strand DNA breaks through the formation of camptothecin 11–TOPO‐1–DNA complexes. A preclinical study has demonstrated irinotecan to be not only a feasible addition to 5‐FU chemotherapy, but also a potent radiosensitizing agent in colorectal cancer, even under hypoxic conditions.…”
Section: Additional Chemotherapy Agents To Enhance Radiosensitivitymentioning
confidence: 99%